Changes in the sexual health behaviours of New Zealand secondary school students, 2001–2012: findings from a national survey series. (3rd July 2016) - Clark, Terryann C.; Lucassen, Mathijs F.G.; Fleming, Theresa; Peiris‐John, Roshini; Ikihele, Amio; Teevale, Tasileta; Robinson, Elizabeth; Crengle, Sue
Abstract: Objective : To describe trends in self‐reported sexual and reproductive health behaviours among New Zealand secondary school students. Methods : Nationally representative health and wellbeing surveys conducted in 2001 (n=9, 699), 2007 (n=9, 107) and 2012 (n=8, 500) were analysed. Logistic regressions were used to explore variations in sexual health outcomes between 2001 and 2012. Results : 'Ever had sex' (−6.9%, p <0.001); 'currently sexually active' (− 2.3%, p <0.001); 'always use condoms' (−3.3%, p =0.006); 'condoms at last sex' (−7.0, p =0.002); 'contraception at last sex' (−5.8%, p <0.001) and sexually transmitted infections (−0.3%, p =0.001) have reduced over time. 'Always use contraception' did not change significantly (−1.4%, p =0.514) over time. Māori (OR 0.7), Pacific (OR 0.5) and socioeconomically deprived students (OR 0.7) less frequently used condoms. Māori (OR 0.6), Pacific (OR 0.4), Asian (OR 0.5), younger (OR 0.6), and socioeconomically deprived (OR 0.6) students less frequently used contraception. Conclusions : Students in 2012 were more likely to delay sexual activity, but were less likely to use condoms and contraception consistently, compared to students in 2001. Declining contraceptive use over an 11‐year period suggests that current strategies are inadequate, particularly for Māori, Pacific and socioeconomically deprived students. Appropriate and accessible sexual and reproductive health services are urgently required.